Analisis Pengelolaan Lingkungan IKM Otomotif dengan Simbiosis Industri - Yunita Ismail (President University, 2016)
The application of industrial symbiosis approach requires collaboration and synergy among the perpetrators. At IKM automotive components collaboration and synergy has occurred in order to meet the production process as the supply chain. Therefore the aim of this study was to analyze and implement synergies between SME development efforts in the automotive components KIJ and its surroundings; to analyze the management of waste, energy consumption, water consumption and by-products among SMEs in the automotive component and surrounding KIJ; and analyze the formation of industrial symbiosis in SME automotive components KIJ and surrounding areas. The sampling method is done deliberately by 30 IKM automotive parts and used questionnaires to obtain data. Data were analyzed using multiple regression analysis to obtain the effect of the independent variable (energy consumption, water consumption, waste and byproducts) to the dependent variable (sustainability). Data analysis showed that cooperation between SMEs of automotive components has occurred but is still limited to business cooperation has not been on the cooperation of environmental management. Variable waste management and water consumption significantly affect sustainability, because both activities shown by these two variables have been implemented by the SME automotive components. Variable energy consumption and by-products did not significantly affect the sustainability, because the energy consumption activities and byproducts in the automotive component SMEs have not been implemented. Industrial symbiosis approach as an approach to environmental management can be carried out among SMEs of automotive components, but still a lot of support is needed.